2018
DOI: 10.1016/j.carj.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Staging Computed Tomography in Patients with Noncurative Laparotomy for Periampullary Cancer: Does Nonstructured Reporting Adequately Communicate Resectability?

Abstract: Periampullary cancer (PC) is a term encompassing malignancies that originate near the ampulla of Vater. It includes cancers of the head and neck of the pancreas, distal common bile duct, second part of the duodenum, and the ampulla itself. Differentiating between these entities, even with biopsy, is often not possible. Therefore, PC is managed identically to pancreatic adenocarcinoma, the fourth leading cause of cancer death in the United States despite representing only 3.1% of new cancer diagnoses [1]. Surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…[20][21][22] More targeted studies have found that sub-specialist reporting of PDAC resulted in greater clarity regarding resection attempts. 21,23 Sub-specialist review often upstages patients and thus prevents unsuccessful resection attempts. 17,19 Given the importance of accurate initial PDAC imaging staging, this study investigated applied CT scanning technique and discrepancies between initial versus sub-specialist radiologist reporting regarding synoptic template usage, report completeness and staging in real-world setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] More targeted studies have found that sub-specialist reporting of PDAC resulted in greater clarity regarding resection attempts. 21,23 Sub-specialist review often upstages patients and thus prevents unsuccessful resection attempts. 17,19 Given the importance of accurate initial PDAC imaging staging, this study investigated applied CT scanning technique and discrepancies between initial versus sub-specialist radiologist reporting regarding synoptic template usage, report completeness and staging in real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies examining discrepancies in PDAC found reporting discrepancies in 31–32% of cases and concluded that second interpretation was a cost‐effective method of determining resectability in patients 20–22 . More targeted studies have found that sub‐specialist reporting of PDAC resulted in greater clarity regarding resection attempts 21,23 . Sub‐specialist review often upstages patients and thus prevents unsuccessful resection attempts 17,19 …”
Section: Introductionmentioning
confidence: 99%